The impact of break duration, time of break onset, and prior shift duration on the amount of sleep between shifts in heavy vehicle drivers. (4th October 2022) - Harris, Rachael; Beatty, Caroline J.; Cori, Jennifer M.; Spitz, Gershon; Soleimanloo, Shamsi Shekari; Peterson, Scott A.; Naqvi, Aqsa; Barnes, Maree; Downey, Luke A.; Shiferaw, Brook A.; Anderson, Clare; Tucker, Andrew J.; et al.
Summary: This study aimed to examine the impact of break duration between consecutive shifts, time of break onset, and prior shift duration on total sleep time (TST) between shifts in heavy vehicle drivers (HVDs), and to assess the interaction between break duration and time of break onset. The sleep (actigraphy and sleep diaries) and work shifts (work diaries) of 27 HVDs were monitored during their usual work schedule for up to 9 weeks. Differences in TST between consecutive shifts and days off were assessed. Linear mixed models (followed by pairwise comparisons) assessed whether break duration, prior shift duration, time of break onset, and the interaction between break duration and break onset were related to TST between shifts. Investigators found TST between consecutive shifts (mean [SD] 6.38 [1.38] h) was significantly less than on days off (mean [SD] 7.63 [1.93] h; p  < 0.001). Breaks starting between 12:01 and 8:00 a.m. led to shorter sleep ( p  < 0.05) compared to breaks starting between 4:01 and 8:00 p.m. Break durations up to 7, 9, and 11 h (Australian and European minimum break durations) resulted in a mean (SD) of 4.76 (1.06), 5.66 (0.77), and 6.41 (1.06) h of sleep, respectively. The impact of shift duration prior to the break and the interaction between break duration and time of break were not significant. HVDs' sleep between workdays is influenced independently by break duration and time of break onset. This naturalistic study provides evidence that current break regulations prevent sufficient sleep duration in this industry. Work regulations should evaluate appropriate break durations and break onset times to allow longer sleep opportunities for HVDs.